Pengaruh Sistem Informasi Pemasaran terhadap Kepuasan Konsumen - Arpin Dalimunthe; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
This study aims to determine the description of the marketing information system that is applied to Cv. Berjaya Medan and analyze the problems of the current system for development in the form of a marketing information system design for promotion. This research was conducted in the marketing section of Cv. Berjaya Medan which is located in Medan. The type of research used is qualitative research with an action research approach. Sources of data used are primary data and secondary data obtained by using data collection methods in the form of observation, interviews, and documentation. These weaknesses include brochures being less effective and efficient in providing information to prospect customers; recommendations from existing customers are not supported by complete sources of information that can be provided when needed; limited marketing reach; existing computers and networks have not been utilized.Keywords: Information Systems, Marketing, Consumer Satisfaction